Manajemen Lembaga Pengembangan Tilawatil Quran (LPTQ) Dalam Pembinaan Qari’ Dan Qari’ah - Muhammad Zaki; Husain Ritonga; Minnah Elwiddah (Institut Agama Islam Negeri Bengkulu, 2021)
Abstract: Management of the Tilawatil Quran Development Institute (LPTQ) in Guiding Qari' and Qari'ah.The aim of this article is to find out about the management of the Tilawatil Quran development institute (LPTQ) in the guidance of Qori and Qoriah. This study used a descriptive qualitative approach carried out at the Tilawatil Quran Development Institute (LPTQ) in Tebo Regency. Data collection techniques are observation, interviews, and documentation. Data analysis techniques in this study consisted of data reduction, data presentation, and data verification. And checking the validity of the data is to use the triangulation technique. The findings show that if the form of management carried out by the Tilawatil Quran Development Institute (LPTQ) in Tebo Regency is good enough, this could be due to the participation of reciter and qari'ah participants in Tebo Regency every year in the MTQ competition from regional to provincial levels. As for the obstacles for these institutions are the absence of special operational funds from the APBD for guidance, still favoring participants from outside the region, dependence on trainers and coaches from outside the region, and the absence of facilities and infrastructure such as offices for qori and qori guidance activities. The efforts made by the institution include planning in the form of regional work meetings, conducting training and training for kafillah, and providing guidance to district LPTQ administrators.Abstrak: Manajemen Lembaga Pengembangan Tilawatil Quran (LPTQ) Dalam Pembinaan Qari’ Dan Qari’ah.Tujuan penulisan artikel ini adalah untuk mengetahui tentang manajemen lembaga pengembangan tilawatil Quran (LPTQ) dalam pembinaan Qori dan Qorian, Kajian ini menggunakan pendekatan kualitatif deskriptif yang dilaksanakan di Lembaga Pengembangan Tilawatil Quran (LPTQ) Kabupaten Tebo. Teknik pengumpulan data yaitu observasi, wawancara, dan dokumentasi. Teknik analisis data pada kajian ini terdiri atas reduksi data, penyajian data, dan verifikasi data. Serta pengecekan keabsahan data adalah menggunakan teknik triangulasi. Hasil temuan dalam kajian ini memperlihatkan bila bentuk manajeman yang dilakukan oleh Lembaga Pengembangan Tilawatil Quran (LPTQ) Kabupaten Tebo sudah cukup baik, perihal ini bisa atas keikutsertaan peserta qari’ dan qari’ah Kabupaten Tebo setiap tahun pada lomba MTQ baik dari tingkat daerah hingga provinsi. Adapun yang menjadi kendala bagi pihak lembaga tersebut adalah tidak adanya dana operasional khusus dari APBD untuk pembinaan, masih mengutuskan peserta dari luar daerah, ketergantungan pelatih dan pembina dari luar daerah, serta tidak adanya sarana dan prasaran seperti kantor dan untuk kegiatan pembinaan qori dan qori’ah. Upaya yang dilakukan oleh pihak lembaga ialah dengan cara melakukan perencanaan dalam bentuk rapat kerja daerah, Melakanakan Pembinaan / TC kafillah, dan melakukan pembinaan kepada pengurus LPTQ Kecamatan